Utilizing Digital Comics in College Students’ Grammar Class - Dias Tiara Putri Utomo; Finaty Ahsanah (Yayasan Visi Intan Permata, 2020)
The utilization of digital comics in this pandemic situation may become a valuable solution. In fact, many challenges and obstacles faced by students regarding the implementation of online learning. This research aimed at investigating the utilization of digital comics in college students’ online grammar class as well as students’ responses. The research design was practical action research which followed Mills’ model (Creswell, 2012). The participants were 36 nursing college students of a university in Lamongan. The instruments used were observation notes, questionnaire, and student-made comics (artifacts). Then, the data from observation notes and student-made comics were analyzed by Miles, Huberman, & Saldana’s (2014) framework for qualitative data analysis while the data from questionnaire were analyzed by using coding to draw conclusion. The results of the study indicated that (1) there are 4 (four) major steps in utilizing digital comics in grammar learning and (2) students showed positive responses to the utilization of digital comics in learning English grammar indicated by the results of questionnaire. It is expected that educators can take advantage of digital applications such as digital comic makers to deal with online classroom.